Fatigue life prediction on heat treated low carbon steel and aluminium - Mohd Ihsan, Ab Rahim (2012)
This research is to find the fatigue life prediction on low carbon steel and aluminum. The objective of this project is to find the fatigue life of the different material which is low carbon steel and aluminum. The second objective is to find out the effect of heat treatment to the fatigue life of the material. The annealing and quenching heat treatment is investigated in this research. The optical microscope and the fatigue test machine was use in assisting for completing the research. The low carbon steel properties has the higher strength compare to aluminum due to the higher fatigue life. The changing of the microstructure due to heat treatment has changing the strength and surface fracture of the material based on type of heat treatment. The annealing process have reduce the strength of the material but the quenching process has increase the strength of both material.